1968
DOI: 10.1002/zaac.19683610104
|View full text |Cite
|
Sign up to set email alerts
|

Über Phosphorsäuren niederer Oxydationszahl. X. Austauschreaktionen in wüsseriger Lösung

Abstract: ‐Säure reagiert in wässeriger Lösung mit Orthophosphat, nicht zu Pyrophosphat, sondern in Form einer Austauschreaktion entsprechend wie durch Einsatz von radioaktiv markiertem Orthophosphat oder radioaktiv markierter ‐Säure nachgewiesen wurde. Neben der Austauschreaktion erleidet die ‐Säure ein gewisses Maß an Hydrolyse. Pyrophosphat reagiert mit Orthophosphat in ähnlicher Weise. jedoch unter erheblich energischeren Bedingungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The reactions of 5'-DFUR and Ara C with DP are summarized by Scheme 1. It is known that DP is readily attacked by nucleophilic reagents such as ammonia, fluoride and glucose 1-monophosphate, 9,10,21 and thus, in the reaction presented in this work, the lone electron pair on the hydroxyl group of the -D-furanosyl unit acts as a nucleophile to attack a phosphorus atom on DP.…”
Section: Reactions Of 5'-dfur and Ara C With Dpmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions of 5'-DFUR and Ara C with DP are summarized by Scheme 1. It is known that DP is readily attacked by nucleophilic reagents such as ammonia, fluoride and glucose 1-monophosphate, 9,10,21 and thus, in the reaction presented in this work, the lone electron pair on the hydroxyl group of the -D-furanosyl unit acts as a nucleophile to attack a phosphorus atom on DP.…”
Section: Reactions Of 5'-dfur and Ara C With Dpmentioning
confidence: 99%
“…Blaser and Worms reported that another inorganic reagent, disodium diphosphonate (Na 2 P 2 H 2 O 5 ), reacts with several nucleophiles, such as monophosphate and fluoride, to form new compounds. 9,10 As shown in Fig. 1, DP is phosphonate, in which phosphorus has an oxidation state of +3, and thus this compound contains the P(III)-H bond, which is not found in the monophosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Disodium diphosphonate (DP), Na 2 P 2 H 2 O 5 , is efficient phosphonylating agent to react with several nucleophiles 5,6 . One of the authors reported the phosphonylation of nucleoside 5'-monophosphate 7 and nucleoside 5'-diphosphate 8 by DP.…”
Section: Figure 1 Structure Of L-dopamentioning
confidence: 99%
“…Blaser and Worms reported that another inorganic reagent, disodium diphosphonate (Na 2 P 2 H 2 O 5 ), reacts with several nucleophiles, such as monophosphate and fluoride, to form new compounds. 5,6 As shown in Fig. 1, DP is phosphonate, in which phosphorus has an oxidation number of 3, and thus this compound contains the P(III)-H bond, which is not found in the monophosphate.…”
Section: Introductionmentioning
confidence: 99%